Prehistoric, ancient Near Eastern and Aegean textiles and dress : an interdisciplinary anthology (Ancient textiles series, 2015)
Textile and dress production, from raw materials to finished items, has had a significant impact on society from its earliest history. The essays in this volume offer a fresh insight into the emerging interdisciplinary research field of textile and dress studies by discussing archaeological, iconographical and textual evidence within a broad geographical and chronological spectrum. The thirteen chapters explore issues, such as the analysis of textile tools, especially spindle whorls, and textile imprints for reconstructing textile production in contexts as different as Neolithic Transylvania